Pengaruh Modified Audit Opinion terhadap Financial Constraint - Ilham Yahya; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to investigate and find empirical evidence whether companies that get modified audit opinions tend to be easy or difficult to get funding from outside the company and prove the effect of modified audit opinions on financial constraints. This study uses a panel data model with random effects and is a quantitative study with a hypothesis. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The method used in determining the sample is purposive sampling method. Based on these criteria, as many as 50 companies were selected as samples with a total of observations over four years of 200 firm-years. The independent variable in this study is financial constraint, while the dependent variable is modified audit opinions. The control variables in this study are Size, Leverage, and Growth. The results of the study indicate that Modified audit opinion does not significantly influence financial constraints, meaning Modified audit opinion obtained by the company is not proven to affect the ability of the company to obtain loans. This means that audit opinion does not affect the decision of creditors to provide loans. However, of all types of Modified audit opinions, only an unqualified opinion with an explanatory paragraph about the inconsistency of accounting principles and going concern that negatively affects the decision of creditors in lending.